Molecular spectrum of spontaneous de novo mutations in male and female germline cells of Drosophila melanogaster. - Watanabe, Y.; Takahashi, A.; Itoh, M.; Takano-Shimizu, T. (Genetics, 2009)
We carried out mutation screen experiments to understand the rate and molecular nature of spontaneous de novo mutations in Drosophila melanogaster, which are crucial for many evolutionary issues, but still poorly understood. We screened for eye-color and body-color mutations that occurred in the germline cells of the first generation offspring of wild-caught females. The offspring were from matings that had occurred in the field and therefore had a genetic composition close to that of flies in natural populations. We employed 1554 F(1) individuals from 374 wild-caught females for the experiments to avoid biased contributions of any particular genotype. From approximately 8.6 million alleles screened, we obtained 10 independent mutants: two point mutations (one for each sex), a single deletion of approximately 6 kb in a male, a single transposable element insertion in a female, five large deletions ranging in size from 40 to 500 kb in females, and a single mutation of unknown nature in a male. The five large deletions were presumably generated by nonallelic homologous recombination (NAHR) between transposable elements at different locations, illustrating the mutagenic nature of recombination. The high occurrence of NAHR that we observed has important consequences for genome evolution through the production of segmental duplications.